Centaurea kirmacii (Asteraceae), a new species from southwestern Anatolia, Turkey - Armağan, Metin; Uysal, Tuna (Phytotaxa, 2018)
A new species of Centaurea is described from Turkey. Centaurea kirmacii Uysal & Armağan occurs on limestone slopes in Pinus brutia forests of Gökçukur plateau of Kavaklıdere (Muğla). The new species belongs to C. sect. Pteracantha Wagenitz, and taxonomically its closest relative is C. odyssei Wagenitz. Diagnostic characters of the new species are provided, with an updated key that includes related species of C. sect. Pteracantha in Turkey. The geographical distributions of the new species and its relatives of the same section are mapped.